KREATIVITAS GURU DALAM MENINGKATKAN MOTIVASI BELAJAR KELAS XI IIS SMA TAMAN MULIA SUNGAI RAYA - Novita, Nona; Salim, Izhar; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study would to determined the creativity of sociology teachers in effort to improve the learning motivation a students of class XI IIS 1 SMA Taman Mulia, Sungai Raya. The purpose of this study was to understand how the creativity of sociology teachers in effort to increase a students to motivation in SMA Taman Mulia Sungai Raya. The analysis of this study were presented in descriptive qualitative. The techniques of data collection in this study were, interviews, observation and documentation. The subject of this study was one of the sociology teachers, and all students at XI IIS. The results of the study suggest istthe teacher's creativity in preparing new teaching material in creating something interesting with dexterity, flexibility, originality and elaboration in systematic learning (materialized), the purpose is clear and the application is also clear, so that will make all students always have motivation to learn. Second,  the teacher's creativity uses a concept map strategy (concept mapping) that involves students in learning and using learning media, so all students can study diligently and diligently. Andfactorsinfluence students learning motivation in accordance with the explanation in students will avoid factors influence learning motivation if they have a creative teacher. Keywords: Learning Motivation, Teacher Creativity